Health promotion offices’ role in increasing healthcare workers’ physical activity - Gulyas, Istvan Laszlo; M. Kornyicki, Agota (Egészségfejlesztés, 2022)
Regular physical activity has been a part of our daily lives since prehistoric times. Owing to the effects of the industrial revolution and urbanization, individuals’ physical activity is constantly decreasing. The European Health Interview Survey 2019 has revealed that a quarter of the Hungarian adults do not exercise enough. The introduced program is a workplace health promotion program. Its primary goal is to relieve fatigue and tension caused by everyday activities and revitalize physical and mental performance and ability. The lifestyle change program series consisted of 81 sessions, each lasting for 60 minutes. The program was available for free in the workplace for healthcare workers. Thirty-one people participated at least once during the program series that lasted nearly for one year. With the help of our semiweekly 60 minutes long health promotion program, the participants who regularly participated in the sessions could reach the optimal amount of physical activity, based on the World Health Organization’s recommendation (75-150 minutes of vigorous-intensity per week).